Bibliometric Analysis: Psychology in Sport - Muniandy, Mahadewan; Mohd Rasyid, Nelfianty binti; Abdul Razak, Norsilawati binti; Elumalai, Gunathevan (International Journal of Academic Research in Progressive Education and Development, 2023)
Psychology in sport is a rapidly growing field that examines the influence of psychological factors on athletic performance and overall well-being. Research in this field has identified a range of psychological factors that can impact an athlete's performance, including motivation, self-confidence, anxiety, attention, and goal-setting. This paper aims to do a systematic review using a bibliometric meta-analysis, regarding the role of emotion in sport and identify avenues for future studies. Scopus database was used in the data-gathering phase. PRISMA approach and keyword search were extracted and analyzed. The research resulted in 1906 articles combinations of the following keywords: ‘psychology’, ‘in’, and ‘sports. This bibliographic data of articles published in the journals over the three years (2020-2023) were extracted. VOS viewer was used to analyzing the data contained in all artciles which published in English language. Thus, in this article four items was analysed such as year of publication, subject area, countries, afilition and more related with article publication. While the findings show that the utilization and acknowledgment psychology in sport effects the performance of the athletes. Furthermore, data showed psychology is an essential skill for athletes to deliver the best achievement. Moreover, researchers should examine the relationship between types of sports and effects of psychology in sport.